2015
DOI: 10.1051/0004-6361/201527031
|View full text |Cite
|
Sign up to set email alerts
|

An ALMA survey for disks orbiting low-mass stars in the TW Hya Association

Abstract: We carried out an ALMA survey of 15 confirmed or candidate low-mass (<0.2 M ) members of the TW Hya Association (TWA) with the goal of detecting molecular gas in the form of CO emission, as well as of providing constraints on continuum emission due to cold dust. Our targets have spectral types of M4-L0 and hence represent the extreme low end of the TWA's mass function. Our ALMA survey has yielded detections of 1.3 mm continuum emission around 4 systems (TWA 30B, 32, 33, and 34), suggesting the presence of cold… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 42 publications
(69 reference statements)
4
24
0
Order By: Relevance
“…Furthermore, most of the newly discovered TWA candidates that are of late-M and L-type also display evidence for disks (Rodriguez et al 2015). The extant data for the TWA hence suggest that disk survival times may be longer for ultra-low mass stars and brown dwarfs than for higher-mass (early-type) M stars-a result that would be consistent with studies of the Upper Sco region (age ∼10 Myr; Scholz et al 2007;Luhman & Mamajek 2012, and references therein).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Furthermore, most of the newly discovered TWA candidates that are of late-M and L-type also display evidence for disks (Rodriguez et al 2015). The extant data for the TWA hence suggest that disk survival times may be longer for ultra-low mass stars and brown dwarfs than for higher-mass (early-type) M stars-a result that would be consistent with studies of the Upper Sco region (age ∼10 Myr; Scholz et al 2007;Luhman & Mamajek 2012, and references therein).…”
Section: Discussionsupporting
confidence: 75%
“…However, only TWA 30B was detected as a submillimeter continuum source, and none of the three were detected as CO sources, in the Rodriguez et al (2015) ALMA survey of ultralow-mass members and candidate members of the TWA. The CO nondetections imply the gas disks orbiting these three stars have very low masses and/or small radii (0.1 Earth masses and/or 10 au, respectively; Rodriguez et al 2015).…”
Section: Presence or Absence Of Circumstellar Disksmentioning
confidence: 93%
See 1 more Smart Citation
“…CO line emission has been previously found to be fainter than expected from the dust emission, assuming the canonical ISM gas-to-dust and [CO]/[H 2 ] ratios (e.g., Dutrey et al 2003;Chapillon et al 2008;Rodriguez et al 2015;Pericaud et al 2016). This conclusion, from small and biased samples, was recently strengthened in a large and unbiased sample of disks in the Lupus star-forming region (Ansdell et al 2016;Miotello et al 2017) and is confirmed here for a complete survey of disks from the young (2-3Myr) ChaI star-forming region.…”
Section: Co Depletion and Implications For Planet Formationmentioning
confidence: 99%
“…This dust mass could be associated with the disk of UX Tauri C. A similar upper limit can be considered for the component UX Tauri B. Molecular disks have been detected toward a handful of low mass or substellar objects. Some examples are IC 348-SMM2E (Palau et al 2014), TWA 34 (Rodriguez et al 2015), Rho Oph 102 (Ricci et al 2012) and 2MASS J04442713+2512164 (Ricci et al 2014). However, none of these disks seem to be associated with a multiple system as UX Tauri.…”
Section: Dust and Gas Massmentioning
confidence: 99%